PENGARUH KONDISI FUNDAMENTAL DAN INFLASI TERHADAP HARGA SAHAM PADA PERUSAHAAN SUB SEKTOR PERKEBUNAN TAHUN 2016-2018. - Jumriaty Jusman; Sinta Devit Puspitasari Sinta Devit Puspitasari (Jurnal Ilmu Ekonomi dan Bisnis, 2020)
The objective of this research is to find out the influence of financial fundamental and macroeconomic factors on stock price. Financial fundamental factors used are ROA, CR, and EPS, while the maroeconomic factor used is inflation.Using purposive sampling method, found 7 companies from 18 plantation sub sector listed in Indonesian Stock Exchange since 2016 until 2018. Data was proced and analyzed by multiple linear regression analysis and prior to the classic assumption test such as normality, multicolinearity, heteroskedasticity, and autocorrelation. The result indicates that simultaneously, ROA, CR, EPS, and inflation have significant influence on stock price. By partially, EPS have significant influence on stock price, while ROA, CR and inflation have insignificant influence on stock price. Keywords: ROA, CR, EPS, Inflation